Wacana Nilai-Nilai Keadilan Gender Di Web Swararahima.com - Putri, Elsa Tania; Junaedi, Jujun; Tresnawaty, Betty (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The purpose of this writing is to find out about the value of gender justice on the Swara Rahima digital da'wah website using a qualitative approach with the Teun A Van Dijk discourse analysis method. This type of research uses media text analysis which implements technical analysis and in-depth literature studies with a research locus on the object of media studies. In this method, there are 3 important components, namely: macrostructure, superstructure, and microstructure. The results of this study are first, the macrostructure of gender justice values which includes the content or big ideas that are carried out in a discourse; second, the superstructure is the topic of discourse on the value of gender justice which is arranged systematically; third, the microstructure of gender justice values which includes semantic elements, syntactical elements, stylistic elements, and rhetorical elements.